FEMINISM IN SUZANNE COLLINS’ NOVEL THE HUNGER GAMES - Romadon, Emha Fadlan; Siwi, Purwanto; Pratiwy, Devi (JOURNAL OF LANGUAGE, 2024)
This study explores the feminist themes embedded within Suzanne Collins' The Hunger Games, focusing on the character of Katniss Everdeen as a symbol of resistance and empowerment. The research aims to analyze the different types of feminism manifested in the novel, examining how Collins challenges traditional gender roles and societal expectations through her protagonist. The study applies sociology of literature approach, which considers the social context and implications of literary works, and utilizes feminist theories, including liberal and radical feminism, to interpret Katniss’s journey. The findings suggest that Katniss embodies both liberal and radical feminist ideals, using her defiance of oppressive authority to fight for personal freedom and gender equality. Katniss’s actions, from assuming the role of family provider to resisting the Capitol’s control, exemplify the themes of self-determination, independence, and the rejection of traditional gender norms. The portrayal of Katniss as a resourceful and brave figure, often adopting traits typically associated with masculinity, reveals the novel's critique of gender stereotypes and its call for a more inclusive understanding of strength and leadership. Ultimately, The Hunger Games serves as a powerful narrative for discussing feminism, challenging the boundaries of gender roles, and highlighting the potential for individual actions to spark social change.